Identity Construction of Generation Z Foodie Nano-Influencers as a Personal Branding Strategy - Angela Gaya Noviko; Maylanny Christin (Green Publisher Indonesia, 2026)
This research aims to explore the phenomenon of the influencer profession as a strategic solution for Generation Z in dealing with the high unemployment rate through the use of the digital creative economy. The main focus of this study is to analyze how foodie nano-influencers from Generation Z construct their identities as an instrument to strengthen personal branding on social media. Using a qualitative approach, this study applied Stuart Hall's identity construction theory which views identity as a dynamic process of